Lepidagathis rajasekharae (Acanthaceae), a new species from the Seshachalam hills of Eastern Ghats of Andhra Pradesh, India - Prasad, Kothareddy; Reddy, Araveeti Madhusudhana (Phytotaxa, 2020)
A new species of Lepidagathis, L. rajasekharae is reported from the Seshachalam hills of Kadapa district, Andhra Pradesh, India. The new species is closely allied to L. fasciculata but differs in many attributes which are discussed here. A detailed description, photographs and conservation status are provided for the new species.